[PP.20.18] CORRELATION OF BIOMARKERS OF CARDIAC REMODELLING, INFLAMMATION AND MYOFIBROSIS WITH PARAMETERS OF CARDIAC STRUCTURE AND FUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION. (September 2016) - Malek, F.; Vondrakova, D.; Dvorak, J.; Sedlackova, L.; Taborsky, L.; Neuzil, P.
Abstract : Objective: Several studies showed role of novel biomarkers of cardiac remodelling and myofibrosis in prediction of risk of heart silure in patient with arterial hypertension (AH). Aim of the study was to evaluace relation of biomarkers of cardiac remodelling (NT-proBNP, soluble receptor ST2), marker of inflammation ceruloplasmin and marker of myofibrosis (galectin-3) with parameters of cardiac structure and function as assessed by echocardiography. Design and method: Patients population and methods: group of 64 patients (37 males, 27 females, mean age 64 years) with esential AH underwent laboratory examination and echo study same date in hypertsnion clinic. Biomarkers were assessed by RayBio™ Custom Quantibody Array. Dual mode, Pulse-Doppler and Tissue Doppler Imaging were used for the assessment of: cardiac chambers size, left ventricular (LV) ejection fraction, calculation of LV mass index (LVMI) and RWT (relative wall thickness) assessment of LV diastolic function with E/A (early filling velocity to atral contraction velocity) ratio and E/E [Combining Acute Accent] (early filling to mean mitral annulus motion velocity) ratio. Results: Mean NT-proBNP level was 16.5 pmol/ll, sST2 139, 9 pg/ml, galectinu3 1470 pg/ml and ceruloplasminu 200 mg/l. Mean LV EF was 66, 8 % (median 66), E/A ratio 0, 9 (0, 85), E/E [Combining Acute Accent] ratio 6, 8 (6, 3), LVMI 84, 1 (83) g/m2 and RWT 0, 40 (0, 41). NT-proBNP correlated with ceruloplasmin level only (r = 0, 222, but p = 0, 08), other correlation between biomarkers were not significant too. NT-proBNP correlated with urea level (r = 0, 333, p < 0, 01), ceruloplasmin correlated with urea (r = 0, 316, p < 0, 05) and sST2 correlated with uric acid (0, 416, p < 0, 05). Concentration of biomarkers did not correlate with echocardiography parameters. Conclusions: Novel biomarkers of cardiac remodelling, inflammation and myofibrosis do not correlate with parameters of cardiac structure and function in patients with arterial hypertension.